Framers Breeding Practice and Traits of Economic Importance for Indigenous Chicken in Lume District, Oromia Regional State, Ethiopia (Global Journal of Science Frontier Research, 2019)
The study aimed at farmers' breeding practice and traits of economic importance for indigenous chicken in lume district, Oromia regional state, Ethiopia. Random samplings were employed to select sample kebeles based on chicken population and purposively select respondents. Administrations of pretested questionnaire were employed on three kebeles of 90 respondents' scavenging chicken keepers, were interviewed. The kebele respondents' were categorized in to 1st, 2nd and 3rd strata having 1-10, 11-20 or 21-49 chicken, respectively. About 97.8 % of the respondents used their hens to incubate the eggs and brood the chicks. Type of container or material used for incubation was not significantly (p
Keywords: breeding objective; culling; trait preference; village chicken; strata; lume district